The correlation of chronological age and micro ribonucleic acid-135b expression in spent culture media of In vitro fertilisation patient - Tiara Berliana Azzahra; Ririn Rahmala Febri; Pritta Ameilia Iffanolida; Kresna Mutia; Budi Wiweko (Wolters Kluwer Medknow Publications, 2022)
Background: The lack of accuracy in embryo viability assessment methods still remains a challenge to increase the in vitro fertilisation (IVF) success rate. The chronological age and micro ribonucleic acid (RNA)-135b influence the quality of the embryo since microRNA-135b expresses stably in the spent culture media. Therefore, microRNA-135b has the potential to become a non-invasive biomarker of IVF embryo quality. Aims: (1) The aim of this study is to determine the chronological age and microRNA-135b expression distribution of IVF patients. (2) to determine the correlation between chronological age and microRNA-135b expression in spent culture media of IVF patients. Study Setting and Design: An observational study was conducted in Yasmin IVF clinic. Materials and Methods: The chronological age data were collected from the medical records and 31 spent culture media samples from 11 IVF patients were taken on day 5 of embryo culture. We also collected the basal media sample as the control group. The microRNA-135b expression was analysed using quantitative real-time polymerase chain reaction (qPCR) analysis. Statistical Analysis Used: The data analysis was performed using IBM SPSS Statistics 25. Results: The chronological age and microRNA-135b expression were distributed abnormally. There was a significant positive correlation with moderate statistical power between chronological age and microRNA-135b expression in spent culture media. MicroRNA-135b expression increased 4.9-fold in spent culture media than basal media of IVF. Conclusions: The increase of chronological age is followed by the rise of microRNA-135b expression in spent culture media of IVF patients. The microRNA-135b is a potential biomarker to predict IVF embryo quality.